2016
DOI: 10.1016/j.ridd.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of direct care staffs’ attitudes towards aggression of persons with intellectual disabilities

Abstract: Further research is necessary in order to understand how team processes affect the attitude towards aggression of direct care staff. Further it is recommended to provide direct care staff with knowledge about mental disorders in clients with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Another explanation may be that male and female staff display different behavioural tendencies in contact with their clients with ID. For instance, studies by Knotter, Wissink, Moonen, Stams, and Jansen (2013) and Knotter, Stams, Moonen, and Wissink (2016) showed that teams with a higher proportion of male staff showed more negative attitudes towards aggression and used more intrusive and coercive interventions than teams with a lower proportion of male staff (or female only teams) when confronted with aggressive behaviour of their clients with ID. In particular team dynamics might account for this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation may be that male and female staff display different behavioural tendencies in contact with their clients with ID. For instance, studies by Knotter, Wissink, Moonen, Stams, and Jansen (2013) and Knotter, Stams, Moonen, and Wissink (2016) showed that teams with a higher proportion of male staff showed more negative attitudes towards aggression and used more intrusive and coercive interventions than teams with a lower proportion of male staff (or female only teams) when confronted with aggressive behaviour of their clients with ID. In particular team dynamics might account for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It was remarkable that none of the training programs included in our meta-analysis focused on training team beliefs and team interaction of direct care staff (Knotter et al, 2013). Besides a functional analysis of the clients' behaviour which "challenges" the relation with an individual direct care worker in the environment in which the behaviour occurs, it is recommended to investigate the interactions in the team (attitude and team climate) and organization characteristics (support, culture, beliefs) on staff-client interactions (Knotter et al, 2016).…”
Section: Recommendationsmentioning
confidence: 99%
“…Interventions may also focus on the environment of the person with an ID. For example on the skills of direct support workers in trying to reduce, manage, or cope with the challenging behaviors (Cox et al 2015, van Oorsouw et al 2013, Stoesz et al 2016, Zijlmans et al 2015 or focus on the team climate (Knotter et al 2016, Willems et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…MLMs and GEEs have both been used to account for clustering caused by a hyper-ordinate structure. For example, MLMs have been used to analyse data clustered because of nesting of parents in couples (Garcia-Lopez et al, 2016;Hartley & Schultz, 2015;Jones et al, 2014;Langley et al, 2017;Pottie et al, 2009), families in households (Pottie et al, 2009), individuals with ID in community homes (Qian et al, 2015), support staff in organizations (Knotter et al, 2016). GEEs have been used to account for clustering caused by carers nesting within households (Totsika et al, 2017), multiple births nesting within women (Brown et al, 2016), or twins nesting within families (Cheng et al, 2015).…”
Section: Use Of These Modelling Approaches In Idd Researchmentioning
confidence: 99%